The Validity of Multiple Representations-Based Blended Learning Program to Stimulate Complex Problem Solving and Reduce Learning Loss - Munadhirotul Azizah; Kartini Herlina; Abdurrahman Abdurrahman (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims to describe the validity of multiple representations-based blended learning programs to stimulate complex problem-solving and reduce student learning loss. The products developed for validation are in the form of syllabi, Lesson Plans, Electronic Student Worksheets (e-Worksheet), and e-Handouts. This type of research includes Research and Development (R&D) using the ADDIE development design which consists of five steps, namely analysis, design, development, implementation, and evaluation. This research is limited to the development stage. The analysis phase is the problem analysis step. The design stage is designing product development. The development stage, namely product development, is carried out by product validation by an expert validator using a validity test sheet instrument in the form of a questionnaire. Validation scores are accumulated to obtain validity values. The results of the investigation based on expert validation prove that the learning program developed is in the category of very high validity. This shows that this learning program is worth experimenting with in teaching and learning activities to find out the practicality and effectiveness of the product in stimulating complex problem-solving and reducing learning loss